Effect of rotation speed and pulling rate on physical properties of titanium-doped sapphire single crystals - Jainal, Mohammad Nabil (2013)
Titanium-doped sapphire single crystals with 0.20 weight percentage of dopant were successfully produced by using the Automatic Diameter Control-Crystal Growth System based on the Czochralski technique. Group A crystals were produced at a constant pulling rate of 1.50 mm h-1 and a rotational speed (8-24) rpm and Group B crystal were produced at a constant rotational speed of 15 rpm and pulling rate (0.75-1.75) mm h-1. The presence of macroscopic defects such as gas bubbles and inclusions were found in the crystals produced at low rotation speed and at high pulling rate. XRD spectra of the crystals identified synthetic corundum as the main phase of the crystals and Al2TiO5 as the second phase. EDAX analysis showed the presence of Al, O and Ti element. Temperature, control power and growth rate were investigated for their correlation on the growth process and crystal diameter profile. When the rotation speed was increased, Group A crystals showed an increase in density from 3.963 g cm-3 to 3.999 g cm-3. For group B crystals, the density decreased from 3.988 g cm-3 to 3.955 g cm-3 with increasing pulling rate. The porosity of the Group A crystals was found to decrease from 0.27% to 0.08% with increasing rotation speed. Group B crystals showed an increase in porosity from 0.09% to 0.44% with increasing pulling rate. From Vickers hardness test, the hardness of Group A crystals increased from 855 HV to 1698 HV with an increase in rotational speed. A decreased in hardness from 1439 HV to 845 HV was observed with increasing pulling rate for Group B crystals. The Young’s Modulus of Group A crystals increased from 1542 MPa to 2069 MPa with increasing rotation speed. However, when the pulling rate was increased for the Group B crystals, the Young’s Modulus was found to decrease from 2002 MPa to 1311 MPa.